2009
DOI: 10.1021/ac901588t
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Nanoscale Imaging of Polymer Bulk-Heterojunction by Scanning Electrical Potential Microscopy and C60+ Cluster Ion Slicing

Abstract: Solution-processable fullerene and copolymer bulk-heterojunctions are widely used as the active layer of solar cells. It is known that the controlled phase-separation in the film provides a pathway for carrier transportation and is crucial to efficiency. In this work, scanning electrical potential microscopy (SEPM) is used to examine the surface distribution of [6,6]phenyl-C61-butyric acid methyl ester and poly(3-hexylthiophene), which form the bulk-heterojunction. Because the two components have different ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…Co‐sputtering with a 10 kV C 60 + and a 0.2 kV Ar + beam is known to preserve the chemical structure of the remaining surface for various organic/polymeric materials . Using the co‐sputtering beam as the ionization source, molecular D‐SIMS spectra were also acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Co‐sputtering with a 10 kV C 60 + and a 0.2 kV Ar + beam is known to preserve the chemical structure of the remaining surface for various organic/polymeric materials . Using the co‐sputtering beam as the ionization source, molecular D‐SIMS spectra were also acquired (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The apparatus is based on a PHI 5000 VersaProbe (ULVAC‐PHI, Chigasaki, Japan) scanning X‐ray microprobe system operated at a base pressure of <1 × 10 –7 Pa, which was achieved by evacuation using ion getter pumps. The Ar + ion source was operated at 0.2 kV and 300 nA (measured on an Au target) using a floating voltage of 500 V. A voltage setting of 0.2 kV has been previously found to preserve the chemical structure of the remaining surface for various organic/polymeric materials while yielding a more stable sputtering rate . The ray path contained a 1° bend to filter fast Ar atoms.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…By stacking the images acquired at different sputtering times as in the sputter‐and‐view scheme, the 3D composition was obtained. In previous studies, it has been shown that C 60 + cluster ion beams do not alter the remaining surface of P3HT:PCBM (poly(3‐hexylthiophene‐2,5‐diyl:[6,6]‐phenyl‐C61‐butyric acid methyl ester) blends significantly, and it has been confirmed that C 60 + sputtering can be used to profile organic solar cells and OLEDs . On the other hand, it is known that C 60 + leaves a small amount of residual amorphous carbon on the surface .…”
Section: Methodsmentioning
confidence: 95%